Wastewater Characterization and pH Neutralizing Effect of Adsorbents: A Case Study of Concrete Wash Wastewater from a Ready-Mix Plant - Adhin Harum Wulaningtyas; Ni Nyoman Nepi Marleni (Journal of the Civil Engineering Forum, 2023)
This study aims to characterize washed concrete wastewater and examine the effectiveness of three different adsorbents in reducing its high alkalinity and metal contents. It is important to note that proper treatment is essential before discharging wastewater into water bodies to prevent any negative impact on the environment. Therefore, in this study, an adsorption scenario was conducted to obtain optimum treatment for washed concrete wastewater. The objectives of this study are as follows (1) to determine the typical characteristics of washed concrete wastewater based on the parameters outlined in the Regulation of the Ministry of Environment of Indonesia No 5 of 2014 and (2) to assess the performance of different adsorbents. Three wastewater samples were obtained from a ready-mix plant and then tested in the laboratory. The initial test was conducted to identify influent characteristics, and from this test, it was found that only the pH level exceeded the specified standard. Following this, the study then assessed the ability of three adsorbents to reduce the pH level in washed concrete wastewater using the batch test in Duplo. The pH level was measured at 0.25, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, and 24 hours. The three adsorbents tested were activated carbon, clay brick, and dried domestic sewage sludge. The result shows that dried domestic sewage sludge was the most effective at reducing alkaline wastewater due to its acidic pH. Therefore, it has the potential to replace other commercial adsorbents and reduce the problem of sludge disposal. Further research on this material is recommended, such as evaluating its performance in a more solid form, such as brick, and assessing its contamination potential.